PERANAN ANGGOTA KELOMPOK WANITA TANI (KWT) DALAM MEWUJUDKAN DESA AGROWISATA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Yudia Anggun Kirana; Irwan Effendi; Serly Silviyanti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to determine the role of Woman Farmer Group (KWT) members and factors related to the role of KWT in actualizing Sungai Langka as an Agrotourism Village.  The research location was chosen purposively in Sungai Langka Village of Gedong Tataan Sub-district of Pesawaran Regency.  Respondents were 61 respondents using Proportional Random Sampling.  This research was conducted from January to February 2018.  Data analysis method used descriptive method with quantitative approach.  To answer the first purpose used descriptive analysis, and the second goal by using a quantitative approach of Rank Spearman analysis method.  The results indicated that the role level of KWT members in mini jackfruit planting and handicraft production is included in a low classification, the roles of KWT members in the manufacture of vegetable quoting galleries, fruit pickling and in Small and Medium Enterprises processing of agricultural products are included in medium classification, KWT in actualizing as Sungai Langka Agrotourism Village is generally included in the middle classification. Factors associated with the role of KWT members in actualizing the Agrotourism Village Sungai Langka are the motivation, cosmopolite character, and the level of knowledge.  Whereas, the age and level of education were not significantly related to the role of KWT members in actualizing Sungai Langka Village as the Agrotourism Village. Key words: agrotourism village, KWT members, role